The The Effect of Using Different Anticoagulant Types for Determination of Esomeprazole Levels in Human Plasma by High-Performance Liquid Chromatography - Mardhiani, Rizka; Harahap, Yahdiana; Sitepu, Eme Stepani; Sunarsih (Jurnal Multidisiplin Madani, 2023)
Esomeprazole is a Proton Pump Inhibitor (PPI) drug formulated in delayed-release tablets, that are included in the mandatory bioequivalence test. In vitro method validation used human plasma from the Indonesian Red Cross that used citrate as an anticoagulant. In the implementation of in vivo study, usually using human plasma used EDTA or heparin as an anticoagulant. This study aims to evaluate the effect of using anticoagulant types that may affect the analysis of esomeprazole in human plasma. Optimum chromatographic conditions used column C18 SunfireTM (5 μm, 250 mm x 4.6 mm); column temperature 40°C; mobile phase acetonitrile - phosphate buffer (40:60% v/v) pH 7.6; 1.0 mL/min flow rate with lansoprazole as an internal standard and wavelength 300 nm (PDA). The extraction was carried out by liquid-liquid extraction method using 500 μl plasma and 5 ml dichloromethane as extraction solvent. The result showed that the concentration range of calibration curve linearity in 5 – 1500 ng/mL. Recovery and broad peak response data of esomeprazole in plasma have significant differences between heparin-EDTA and citrate-EDTA anticoagulants (p<0.05), but there is no significant difference for the stability test. In conclusion, heparin is better than EDTA as an anticoagulant for esomeprazole bioanalysis